Strain-oxygen vacancies coupling in topotactic (La,Sr)CoO3-δ thin films - Yichen Wu; Victor Rosendal; Milica Vasiljevic; Imran Asghar; Vincenzo Esposito (Applied Surface Science Advances)
Oxygen defect engineering is a widely used approach for tuning physical properties in oxides. Multivalent transition metal oxide La0.7Sr0.3CoO3-δ (LSCO) shows oxygen vacancy-driven metal-to-insulator transition (MIT) due to topotactic phase transition and its high oxygen vacancy tolerance. Here, we introduce strain as a new degree of freedom to study the strain-oxygen vacancy coupling effects and elucidate its impact on the electronic property in oxygen-deficient LSCO epitaxial thin films grown on SrTiO3 (100) single crystal. By combining the experimental results with density functional theory plus U (DFT+U) calculations, we reveal that 2.1 % in-plane tensile strain can stabilize the insulating state of LSCO with a surprisingly low concentration of oxygen vacancies, <0.5 %. This study reveals that the MIT in LSCO is governed by the combination of oxygen vacancies and strain, offering the potential for additional tuning knob of the material's electronic properties.